Optimization of Tissue Culture Medium for Little-leaf Mockorange (Philadelphus microphyllus A. Gray) by Adjusting Cytokinin and Selected Mineral Components - Razieh Khajehyar; Robert Tripepi; Stephen Love; William J. Price (HortScience, 2023)
Little-leaf mockorange is a native plant species with desirable characteristics for landscape use. The need to conserve specific genotypes and the difficulty of seed propagation and stem cutting propagation make axillary shoot micropropagation a good option for this species. A series of experiments were completed individually with the goal to improve in vitro propagation protocols by evaluating different types of cytokinins [benzylaminopurine (BA), kinetin (Kin), zeatin (Zea), meta-topolin (MT), and thidiazuron (TDZ)] at 0, 1.1, 2.2, 4.4, or 8.8 µM. Selected minerals (0 to 60 mM or 0 to 45 mM N, 0 to 500 µM or 0 to 100 µM Fe, 0 to 3 mM Ca, 0 to 1.5 mM Mg, or 0 to 1.25 mM P) were also tested separately in the tissue culture medium; the base medium was ½ strength MS in these mineral experiments. At the end of each experiment (8 or 12 weeks), plant growth characteristics including number of axillary shoots, shoot height, and dry weight were determined. Of the six cytokinins tested, Zea produced the largest increase in shoot growth. Supplementation with 1.1 µM Zea resulted in the most shoot dry weight, almost 2.5-fold more than control shoots. Shoots on 0.55, 1.1, or 2.2 µM Zea were at least 64% taller than control shoots. Shoots placed on regular ½ strength MS basal salts, described above, and/or media lacking the nutrient of interest, were used as a positive and negative control treatments. For each separate mineral tested, the best concentration for optimum shoot growth was the concentration of that mineral used in ½ strength MS medium. A medium containing mineral concentrations of 30 mM N, 50 µM Fe, 1.5 mM Ca, 0.75 mM Mg, and 0.625 mM P, and 1.1 µM Zea should be used to produce the optimum in vitro shoot growth of little-leaf mockorange.